2000
DOI: 10.1161/01.atv.20.12.2600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Scavenger Receptor Class A Overexpression in Bone Marrow–Derived Cells on Cholesterol Levels and Atherosclerosis in ApoE-Deficient Mice

Abstract: Abstract-In the arterial wall, scavenger receptor class A (SRA) is implicated in pathological lipid deposition. In contrast, in the liver, SRA is suggested to remove modified lipoproteins from the circulation, thereby protecting the body from their pathological action. The role of SRA on bone marrow-derived cells in lipid metabolism and atherogenesis was assessed in vivo by transplantation of bone marrow cells overexpressing human SRA (MSR1) to apoE-deficient mice.In vitro studies with peritoneal macrophages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 44 publications
4
36
0
2
Order By: Relevance
“…In that study, the mean plasma cholesterol level of the Apoe -/-male mice was 935 mg/dl, which corresponds well with the value (922 mg/dl) we measured in the Apoe -/-mice used in our study. Two studies have also noted that Msr1 expression alters total cholesterol levels in the Apoe -/-mouse model; Suzuki et al showed that loss of Msr1 led to a 40% increase in total cholesterol while Van Eck et al demonstrated that overexpression of Msr1 reduced total cholesterol by a similar fraction (9,17). In addition, using SR-A transgenic mice, Wolle et al showed that overexpression of this receptor suppressed diet-induced increases in lipoproteins that contain apoB (18).…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the mean plasma cholesterol level of the Apoe -/-male mice was 935 mg/dl, which corresponds well with the value (922 mg/dl) we measured in the Apoe -/-mice used in our study. Two studies have also noted that Msr1 expression alters total cholesterol levels in the Apoe -/-mouse model; Suzuki et al showed that loss of Msr1 led to a 40% increase in total cholesterol while Van Eck et al demonstrated that overexpression of Msr1 reduced total cholesterol by a similar fraction (9,17). In addition, using SR-A transgenic mice, Wolle et al showed that overexpression of this receptor suppressed diet-induced increases in lipoproteins that contain apoB (18).…”
Section: Resultsmentioning
confidence: 99%
“…The aortic sinus was embedded and then made into serial cryosections of 7-μm thickness. The atherosclerotic lesions at aortic sinus were stained with ORO as previously described (Van Eck et al 2000). The mean lesion area for each mouse was calculated from four sections.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The lesion size was quantified by measuring Oil-red-O stained area. The mean lesion size for each individual mouse was calculated from four sections, starting at the appearance of the tricuspid valves [40]. SR-A in cells at atherosclerotic lesion was stained with anti-SR-A antibody.…”
Section: Apoementioning
confidence: 99%